IMAGING DEVICE AND ELECTRONIC DEVICE INCLUDING THE SAME (2020)
An imaging device includes a light source operating in response to an optical control signal having a predetermined frequency, a sensor including a plurality of pixels, configured to generate an electrical signal in response to a light reception signal output by the light source and reflected from a subject, and a logic circuit configured to generate first raw data of a spatial domain based on the electrical signal, and an image signal processor configured to convert the first raw data into second raw data of a frequency domain, to select low-frequency data of the second raw data within a frequency band lower than a predetermined reference frequency, to apply a predetermined weighting to the low-frequency data to generate weighted data, and to generate a resultant image based on the first raw data and the weighted data.